Berlin statement on legacy and emerging contaminants in polar regions. (June 2023) - Ebinghaus, Ralf; Barbaro, Elena; Bengtson Nash, Susan; de Avila, Cristina; de Wit, Cynthia A.; Dulio, Valeria; Felden, Janine; Franco, Antonio; Gandrass, Juergen; Grotti, Marco; Herata, Heike; Hughes, Kevin A.; et al.
Abstract: Polar regions should be given greater consideration with respect to the monitoring, risk assessment, and management of potentially harmful chemicals, consistent with requirements of the precautionary principle. Protecting the vulnerable polar environments requires (i) raising political and public awareness and (ii) restricting and preventing global emissions of harmful chemicals at their sources. The Berlin Statement is the outcome of an international workshop with representatives of the European Commission, the Arctic Council, the Antarctic Treaty Consultative Meeting, the Stockholm Convention on Persistent Organic Pollutants (POPs), environmental specimen banks, and data centers, as well as scientists from various international research institutions. The statement addresses urgent chemical pollution issues in the polar regions and provides recommendations for improving screening, monitoring, risk assessment, research cooperation, and open data sharing to provide environmental policy makers and chemicals management decision-makers with relevant and reliable contaminant data to better protect the polar environments. The consensus reached at the workshop can be summarized in just two words: "Act now!" Specifically, "Act now!" to reduce the presence and impact of anthropogenic chemical pollution in polar regions by. Establishing participatory co-development frameworks in a permanent multi-disciplinary platform for Arctic-Antarctic collaborations and establishing exchanges between the Arctic Monitoring and Assessment Program (AMAP) of the Arctic Council and the Antarctic Monitoring and Assessment Program (AnMAP) of the Scientific Committee on Antarctic Research (SCAR) to increase the visibility and exchange of contaminant data and to support the development of harmonized monitoring programs. Integrating environmental specimen banking, innovative screening approaches and archiving systems, to provide opportunities for improved assessment of contaminants to protect polar regions. Highlights: To increase public and political awareness, improved visibility and open access of polar contaminant data is needed. The use of data for chemicals of emerging concern from polar regions, indicating long-range transport potential and persistence, should be enhanced in chemicals management. Closer exchange between the Arctic Monitoring and Assessment Program (AMAP) and the Antarctic Monitoring and Assessment Program (AnMAP) should be fostered. Environmental specimen banks, novel screening approaches and digital sample-freezing platforms should be integrated for improved assessments. Co-development frameworks in a permanent multi-disciplinary platform should be established for the environmental management of polar regions.